Pemikiran Ekonomi dan Kewangan Islam Profesor Dr. Joni Tamkin Bin Borhan: Islamic Economic and Financial Thought of Professor Dr. Joni Tamkin Bin Borhan - Nor Azelan, Suffian Haqiem; Mohd Noh, Mohd Shahid (Online Journal of Research in Islamic Studies, 2023)
Professor Dr Joni Tamkin bin Borhan was a Shariah scholar who has made a great contribution to Islamic economics and finance in Malaysia. He was a Professor in Islamic economics at the Department of Shariah and Economics, Academy of Islamic Studies, University of Malaya. Since the establishment of the first Islamic bank in Malaysia in 1983, the role of Shariah scholars has become increasingly significant, especially in designing the Islamic financial system in Malaysia. This study aims to analyze his ideas and thoughts in Islamic economics and finance. The data was collected from his own UM-Expert database before he passed away. This database is used to share with others of his academic activities and also used as evaluation for his achievements by University of Malaya. In addition, interviews with his wife were also conducted for additional information and confirmation of some relevant facts. As a professor in this field, his views and thoughts regarding the Islamic economic and financial system are something very valuable and need to be highlighted to the highest level.